Detailed clinical assessment of neurological function in symptomatic shipyard workers. Issue 8 (August 1990) - Cherniack, M G; Letz, R; Gerr, F; Brammer, A; Pace, P
Abstract : Forty eight patients with extensive occupational exposure to pneumatic grinding tools were evaluated at a university sponsored occupational health clinic. All patients were interviewed and examined by a physician and assessed neurologically with standard clinical, functional motor, quantitative vibrotactile, and electrodiagnostic tests. Sensorineural symptoms were nearly universal; 47 patients (98%) reported numbness and tingling of the hands and fingers. Among clinical tests, two point discrimination and 30 Hz vibration perception were most frequently abnormal. In order to evaluate associations between quantitative test results and sensorineural symptoms, patients were stratified into two groups of symptom severity according to a consensus sensorineural staging system. The tests that discriminated best between the groups of more and less symptomatic patients were hand strength dynamometry, and vibrotactile thresholds. Age standardised 120 Hz vibrotactile thresholds were significantly raised in digit II in 41% of hand measurements. Nerve conduction studies were neither significantly different between more and less symptomatic groups nor correlated with clinical and quantitative sensory tests. Twenty five per cent of the patients had slowing of sensory conduction velocities in the median nerve at the wrist (less than 48 m/s). Of this subset of patients only two showed abnormal slowing of the median nerve distal to the wrist, but half also showed ulnar nerve slowing (less than 47 m/s).This observation highlights the difficulty of differentiating median nerve entrapment from diffuse distal neuropathy in workers exposed to vibration and points to the need for concomitant quantitative sensory and functional motor assessment.